1977
DOI: 10.1104/pp.60.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glyphosate on Carrot and Tobacco Cells

Abstract: The growth of suspension-cultured carrot (Daucus carota L.) and tobacco (Nicotiana tabacum L. cv. Xanthi) cells was inhibited by glyphosate (N-[phosphonomethyllglycine). This inhibition was reversed by adding combinations of phenylalanine, tyrosine, and tryptophan or casein hydrolysate. Casein hydrolysate and phenylalanine + tyrosine + tryptophan were the most effective treatments. Reversal of glyphosateinduced inhibition occurred only if the aromatic amino acids were added during the first 8 days of glyphosat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
64
1
1

Year Published

1980
1980
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 11 publications
9
64
1
1
Order By: Relevance
“…Early work (11) showed that glyphosateinduced growth inhibition of duckweed (Lemna gibba) and Rhizobium japonicum could be overcome by supplying aromatic amino acids. Similar results have been reported with Escherichia coli, Chlamydomonas reinhardii, Arabidopsis thaliana, and cultured cells of carrot (Daucus carota), soybean (Glycine max), and tobacco (Nicotiana tabacum) (6,8).…”
supporting
confidence: 73%
See 3 more Smart Citations
“…Early work (11) showed that glyphosateinduced growth inhibition of duckweed (Lemna gibba) and Rhizobium japonicum could be overcome by supplying aromatic amino acids. Similar results have been reported with Escherichia coli, Chlamydomonas reinhardii, Arabidopsis thaliana, and cultured cells of carrot (Daucus carota), soybean (Glycine max), and tobacco (Nicotiana tabacum) (6,8).…”
supporting
confidence: 73%
“…Early work (11) showed that glyphosateinduced growth inhibition of duckweed (Lemna gibba) and Rhizobium japonicum could be overcome by supplying aromatic amino acids. Similar results have been reported with Escherichia coli, Chlamydomonas reinhardii, Arabidopsis thaliana, and cultured cells of carrot (Daucus carota), soybean (Glycine max), and tobacco (Nicotiana tabacum) (6,8).Based on the reversal of glyphosate inhibition by aromatic amino acids, it was proposed that the herbicide may act by reducing the synthesis of these amino acids (11). Glyphosateinduced reductions in the levels of aromatic amino acids have been found in maize roots (9), soybean hypocotyls (4), wheat (16), and buckwheat hypocotyls (10).…”
supporting
confidence: 67%
See 2 more Smart Citations
“…High concentrations of the herbicide inhibited the two initial enzymes of the shikimate pathway, but this inhibition was apparently too slight to account for growth inhibition caused by low glyphosate concentrations. Inhibition by glyphosate of the growth of carrot and tobacco cells was alleviated by the addition of the three aromatic amino acids, but Haderlie et al (15) hesitated to conclude that the synthesis of the aromatic amino acids was inhibited by glyphosate because glyphosate did not appreciably reduce the cellular concentrations of these amino acids. Just recently, Greshoff (14) extended the earlier studies of Jaworski (20) and Haderlie et al (15) with an investigation on glyphosate's growth inhibition of E. coli, Chlamydomonas reinhardtii, carrot and soybean cell cultures, and Arabidopsis thaliana seedlings.…”
mentioning
confidence: 97%